FORMULASI DAN UJI STABILITAS SEDIAAN TONER WAJAH EKSTRAK BUAH PARE (Momordica charantia L) SEBAGAI ANTI JERAWAT DENGAN VARIASI SURFAKTAN - Noor, Muhammad; Malahayati, Siti; Nastiti, Kunti (Jurnal Riset Kefarmasian Indonesia, 2023)
Bitter gourd extract (Momordica charantia L) contains secondary metabolites such as flavonoids, alkaloids, and saponins that can be antibacterial against acne-causing bacteria (Propionibacterium acnes). Momordica charantia L., could make into facial toner preparations to prevent the emergence and worsen acne. It is formulated with various concentrations of polysorbate 20 and performs stability testing. This study aimed at the optimal formula and analyzed the variations in the concentration effect of polysorbate 20 on the bitter gourd extract facial toner preparation. Bitter gourd extract would make into facial toner preparation with variations in the concentration of polysorbate 20. The accelerated stability test with the cycling test method includes before and after organoleptic, homogeneity, viscosity, and pH tests. The organoleptic stability result shows both stable formulas had the same liquid form, clear brown color, and characteristic rose odor. All formulations are stable on homogeneity, in which the particles are evenly mixed. The Formula I viscosity value is constantly stabilized and meets the parameters, while formula II is not but meets the parameters. The pH stability values of both formulas are stable and meet the parameters. Formula I is more optimal than formula II and the difference in surfactant concentration of polysorbate 20 has no effect on organoleptic, homogeneity, and pH but will affect viscosity.